THERAPEUTIC EFFICACY OF ATROPINE AGAINST CHOLINESTERASE INHIBITORS TOXICITY IN CHICKS STRESSED WITH HYDROGEN PEROXIDE - Yaareb J. Mousa; Muna H. I. Al-Zubaidy; Sawsen M. Ameen; Fouad K. Mohammad (Basrah Journal of Veterinary Research)
The aim of this study was to evaluate therapeutic efficacy of atropine in case ofcholinesterase (ChE) inhibitors toxicity in chicks subjected to oxidative stress (OS) withhydrogen peroxide (H2O2). H2O2 at 0.5 % in drinking water induced OS at age of 7-14days in the chicks when given each day for 14 consecutive days. There was no change inthe acute median lethal dose (LD50) for diazinon (7.9 mg/kg, orally) for both H2O(control) and H2O2 groups. The therapeutic efficacy of atropine was decreased (265 %)when measuring the median effective dose (ED50) for treating the diazinon toxicity inH2O group (2.6 mg/kg, i.m.) and in the H2O2 group (9.5 mg/kg, i.m.). The signs of acutediazinon toxicity were found to increase in H2O2 groups when compared to H2O groupand there is slight decrease in plasma and whole brain ChE activities in H2O2 group whenwhen compared to H2O group. The data revealed a decline in atropine efficacy for treatment diazinon toxicity in chicks that suffered from OS status and it is recommendedhere to increase the dose of atropine in this case.